Integrated mangrove aquaculture: The sustainable choice for mangroves and aquaculture? - McSherry, Madeline; Davis, Robert P.; Andradi-Brown, Dominic A.; Ahmadia, Gabby N.; Van Kempen, Malou; Wingard Brian, Susanna (Frontiers in Forests and Global Change, 2023)
Aquaculture production is projected to surpass wild-capture fisheries as the primary source of aquatic animal protein in the near future. Farmed shrimp—which are amongst the most valuable aquaculture commodities—are raised predominantly in Southeast Asia and Latin America in a variety of production systems, spanning from extensive to intensive farming. Shrimp aquaculture has been widely criticized for causing mangrove forest degradation and loss, leading to calls for more sustainable aquaculture approaches that protect mangroves. Here we examine an approach promoted as more sustainable—integrated mangrove aquaculture (IMA): a type of farming where mangroves are planted in or alongside shrimp ponds. We argue that mangroves within IMA shrimp systems provide biodiversity and ecosystem functions and services that are, at best, compromised, especially when compared to intact mangrove forests. Given the rapid adoption of IMA approaches, including advocacy for uptake from many governments and non-governmental organizations, there is an urgent need to ensure that these and other aquaculture systems do not result in any conversion of intact mangrove ecosystems into aquaculture ponds, and to identify any benefits (or lack thereof) provided by IMA systems. The increasing adoption of IMA may offer false promises for managing trade-offs between increasing aquaculture productivity and mangrove forest conservation.